IDENTITAS DAN VISUALISASI PEREMPUAN URBAN INDONESIA DALAM KOMUNIKASI MELALUI MAJALAH FEMINA - Ariani Wardhani (Universitas Trisakti, 2017)
AbstractIdentity and Visualization of Indonesian Urban Women in Femina Magazine Comunication. Femina is a magazine that represents Indonesian women, especially in Jakarta. Femina magazine has been established since 1972 and up to today it is still the preferred magazine by urban women in Indonesia. Fashion (mode) rubric is one of the rubrics that are anticipated by the reader because this rubric presents the most recent lifestyle trend. Fashion (mode) is an inseparable part from women. The identity of urban women in Indonesia could be seen from the symbols that could be found on the mode rubric of the Femina magazine. Analysis through visual data has been carriedout by using symbols that are present on mode rubric of Femina magazine. All of the signs that represent urban women in Indonesia is related and organized into a social domination which present in the community. As a product of visual culture, fashion posses various outlooks, from visual point of view and social facts that occur in the daily life. Analysis of social semiotics was performed using Van Leeuwen’s method used to analyze modality in a multimodal text. The role of identity and representation become the foundation in the outlook of technology shift from printed to digital form of the magazine. The visual strength on Femina magazine possesses collaboration in the representative formulation and identity with the influence of Indonesian urban women. Massively and arbitrarily media presented image regarding women to the generalpublic. The long reach of media enables it to distribute such women images to multiple places and finally produced the view AbstrakIdentitas dan Visualisasi Perempuan Urban Indonesia dalam Komunikasi Melalui Majalah Femina. Femina adalah majalah yang mewakili para perempuan Indonesia terutama di Jakarta. Majalah Femina telah hadir untuk perempuan Indonesia dari tahun 1972 dan sampai saat ini masih menjadi pilihan para perempuan urban di Indonesia. Rubrik mode merupakan salah satu rubrik yang dinanti oleh para perempuan, karenarubrik tersebut menyajikan tentang gaya hidup terkini. Mode merupakan bagian yang tidak dapat dipisahkan dari para perempuan. Identitas perempuan urban di Indonesiadapat dilihat dari tanda-tanda yang terdapat pada rubrik mode majalah Femina. Pembedahan secara visual dilakukan dengan melihat tanda-tanda yang terdapat pada rubrik mode majalah Femina. Keseluruhan tanda-tanda representasi sosok perempuan urban di Indonesia dihubungkan dan diorganisasikan ke dalam bentuk dominasi sosialyang terdapat pada masyarakat. Sebagai produk budaya visual, rubrik mode memilikipandangan dari segi visual dan fakta sosial yang terjadi di sekitarnya.Analisis semiotika sosial dengan pandangan Van Leuween digunakan untuk menganalisis modalitas dalam teks multimodal.Peran identitas diri dan representasi menjadi dasar dalam memandang perubahan teknologi dari majalah cetak ke digital.Kekuatan visual pada majalah Femina memiliki kolaborasi dalam pembentukan representasi dan identitas diri dengan pengaruh perempuan urban Indonesia.Media secara massif dan arbitrer menampilkan citra mengenai perempuan kepada khalayak ramai. Jangkauan media yang luas memampukan media menyebarkan citra yang sama mengenai perempuan ke banyak tempat dan pada akhirnya menyebabkan kesamaan pandangan masyarakat mengenai identitas perempuan.